2023
DOI: 10.1038/s41467-023-36083-1
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle-enhanced X-ray microtomography of the rodent reveals region-specific cerebrospinal fluid circulation in the brain

Abstract: Cerebrospinal fluid (CSF) is essential for the development and function of the central nervous system (CNS). However, the brain and its interstitium have largely been thought of as a single entity through which CSF circulates, and it is not known whether specific cell populations within the CNS preferentially interact with the CSF. Here, we develop a technique for CSF tracking, gold nanoparticle-enhanced X-ray microtomography, to achieve micrometer-scale resolution visualization of CSF circulation patterns dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
(70 reference statements)
2
3
0
Order By: Relevance
“…The perimesencephalic cisterns separate two functionally-distinct regions—the hippocampus and the midbrain. This, in conjunction with the results of our present study showing diffuse 15-nm AuNP movement into only the hippocampal side of the quadrigeminal, and ambient cisterns, but not the midbrain, suggest that these cisterns may serve to facilitate a regionalized CSF-brain parenchyma cross talk [ 34 37 ]. Alternatively, their location in between the LV and 3V may serve as a potential route for inter-ventricular CSF transport and communication [ 21 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The perimesencephalic cisterns separate two functionally-distinct regions—the hippocampus and the midbrain. This, in conjunction with the results of our present study showing diffuse 15-nm AuNP movement into only the hippocampal side of the quadrigeminal, and ambient cisterns, but not the midbrain, suggest that these cisterns may serve to facilitate a regionalized CSF-brain parenchyma cross talk [ 34 37 ]. Alternatively, their location in between the LV and 3V may serve as a potential route for inter-ventricular CSF transport and communication [ 21 ].…”
Section: Discussionsupporting
confidence: 81%
“…After intracardial perfusion sacrifice 10 min post-1.9-nm AuNP injection and 4 h post-15-nm AuNP injection, the entire rodent body was placed in 4% paraformaldehyde at 4° C overnight, embedded in 2% agarose, and imaged within 72 h of sacrifice with a Zeiss Versa 520 X-ray microscope (Carl Zeiss Imaging, White Plains, NY) using a 0.4 × flat panel detector as previously described [ 37 ]. The X-ray source was tuned to 50 kV at 4W to optimally excite gold particles.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, adeno associated virus at 25nm is usually excluded by the BBB/BNB unless leakage is induced, or neurotropic selected serotypes are used (4648). Recent CSF flow studies using both gold and other nanoparticles have shown restricted flow patterns within the CNS for particles of 20-40nm compared to 3-5-4.5nm, further supporting our size selections (5, 6, 49, 50). Therefore, 1.9nm nanogold would be small enough to potentially transverse the BBB/BNB while 15nm nanogold particles should be mostly excluded.…”
Section: Discussionsupporting
confidence: 81%
“…The smaller 1.9nm nanogold traced expected patterns of CSF flow within the central nervous system flowing from the infused ventricles, throughout the brain and spinal cord (Fig. S2) (49). 1.9nm nanogold distribution, however, extended beyond the CNS to the PNS, including distal peripheral nerves (Fig.1,4 and S1).…”
Section: Discussionmentioning
confidence: 95%
“…Recent data suggest that not only local blood supply, but also CSF movement from lateral and third ventricles to neurogenic niches might contribute to adjusting the rate of neurogenesis to actual demand of developing and active brain. 102 Since embryonic and adult neurogenesis has been extensively described in details elsewhere, 103 106 we are going to focus here on a role of BBB and BCSFB in the regulation of adult neurogenesis stimulated in experience-driven brain plasticity and repair of lesioned brain tissue.…”
Section: Integrity Of Brain Barriers and Control Of Adult Neurogenesismentioning
confidence: 99%